Ultra-Wide Field Imaging Characteristics of Primary Retinal Vasculitis: Risk Factors for Retinal Neovascularization. (3rd April 2019) - Sheemar, Abhishek; Temkar, Shreyas; Takkar, Brijesh; Sood, Rita; Sinha, Sanjeev; Chawla, Rohan; Vohra, Rajpal; Venkatesh, Pradeep
ABSTRACT: Aim : To evaluate patterns of retinal vasculitis with ultra-wide field imaging (UWF) and ascertain the risk factors for retinal neovascularization. Methods : Consecutive patients of retinal vasculitis were included prospectively. Patients with retinal vasculitis secondary to uveitis were excluded. UWF was done for all the patients. Retinal involvement was classified into three zones and area of capillary non-perfusion was stratified into clock hours. Results : Two hundred patients were included, 85% ( n = 170) were male. Mean age was 28.99 ± 10.56 years. Clinical examination revealed 65% cases ( n = 130) to be bilateral, while UWF angiography detected 72.5% ( n = 145) to have bilateral involvement. Retinal neovascularization was present in 47% ( n = 188).Presence of posterior disease had very high odds ratio for development of retinal neovascularization as compared to cases restricted to retinal periphery (OR = 45.03, CI = 6.10–332.30, p = < 0.001). Conclusion : UWF imaging is useful in detecting retinal vasculitis, which is otherwise obscure to clinical examination and assessing risk factors for retinal neovascularization.